A Hybrid Spiral Project Based Learning Model for Microprocessor Course Teaching - M., Mohammad Tarik (Kurdistan Journal of Applied Research, 2017)
High demands for technology increase every day. These demands required expert engineers with high skills to keep up with technology demands. Engineering departments need to responded for this requirement to develop their educational methods. researchers began to develop educational methods and measure their effectiveness. This paper develops an educational method to educate microprocessor course. The educational model mixed the spiral method and project based learning to achieve the desirable goal. Educational activities used in the educational method like lecture, lab, and project. also, virtual lab developed to achieve better learning performance. The proposed educational method evaluated in two ways. First, statistical analysis for students’ scores shows significant differences and improvement in the learning outcome. second, students survey shows very positive impact on students learning.